Antibiotic treatment duration for culture-negative sepsis in the pediatric intensive care unit - Kelsey Wehrenberg; Michelle Mitchell; Tracy Zembles; Ke Yan; Liyun Zhang; Nathan Thompson (Cambridge University Press, 2023)
Abstract Objective: Sepsis remains a leading cause of morbidity and mortality in children. There is very limited guidance for sepsis treatment when cultures remain negative. This study sought to determine the effectiveness of short versus long course of antibiotics when treating culture-negative sepsis and assess for subsequent multidrug-resistant organism (MDRO) acquisition. Design: Retrospective cohort study. Setting: Quaternary academic children's hospital. Patients: Pediatric intensive care unit (ICU) patients with culture-negative sepsis receiving a minimum of 72 hours of antibiotics. Methods: Patients found to have culture-negative sepsis from January 2017 to May 2020 were divided into two groups: short and long course of antibiotics. Various demographic and laboratory results were collected for each subject as available. Primary outcomes included mortality and lengths of stay. The secondary outcome was subsequent acquisition of a new MDRO. Results: Eighty-six patients were treated for culture-negative sepsis with 43 patients in both the short- (< or = 7 days) and long-course (>7 days) treatment cohorts. Patients who received a short course of antibiotics had a lower overall mortality than those who received a long course (9.3% vs 25.6% p = 0.047), but there was no difference in 30-day mortality (p > 0.99). Patients in the short-course group had a shorter hospital length of stay (22 vs 30 days p = 0.018). New MDROs were found in 10% of all patients. Conclusions: Treatment of culture-negative sepsis with short-course antibiotics was not associated with worse outcomes in ICU patients. These findings warrant further investigation with a larger, prospective, multi-center study.